1129 Central Sleep Apnea after Hypoglossal Nerve Stimulation. (27th April 2018) - Chan, L C; Chang, M; Aysola, R; Ryden, A; Mendelsohn, A; Zeidler, M
Abstract: Introduction: The emergence of central sleep apnea has been reported when treating obstructive sleep apnea (OSA) with positive airway pressure (PAP), mandibular advanced devices (MAD) or upper airway surgery. We report the emergence of central sleep apnea following OSA treatment with hypoglossal nerve stimulation. Report of Case: A 61 -year-old male with a history of obesity (BMI 31.41) was diagnosed with moderate OSA (REI 27e/hr.). PAP therapy was attempted but not tolerated. An MAD did not improve his symptoms and a repeat portable sleep study with MAD continued to show an REI of 48.8e/hr. with obstructive and central events identified. (49 central apneas, 219 obstructive apneas, 36 hypopneas). A hypoglossal nerve stimulator was implanted after a drug induced endoscopy deemed him an appropriate candidate. Following activation, he completed an in-lab voltage titration up to (+-+) 1.2 V, however residual obstructive and central apneas were observed (AHI 24.71e/hr., 18 central apneas, 3 obstructive apneas, 124 hypopneas) with appearance of Cheyne-Stokes breathing. A follow up portable sleep study a month later continued to show obstructive and central events with an overall REI of 45e/hr. (25 central apneas, 119 obstructive apneas, 74 hypopneas). An awake endoscopy with advanced programming was performed which noted good response to stimulation at the tongue base, however poor response at the soft palate. His configuration was changed to (---) 0.6–1.6V. Follow up PSG titration with new settings demonstrated good control of OSA with an AHI of 2.08/hr. at 1V. Conclusion: Our patient developed central apneic events following implantation of a hypoglossal nerve stimulator for the treatment of obstructive sleep apnea. The pathophysiology behind this phenomenon may be explained by: 1) An unresolved obstruction which may have led to microarousals and overshoot of PaCO2 reduction below the apneic threshold during sleep. 2) Some patients with severe OSA may have an elevated loop gain which may be unmasked after inspiratory flow limitation is relieved, leading to central apneic events. These events eventually may disappear with continuous OSA treatment and eventual resetting of CO2 receptors. In our patient, central apneas resolved following advanced programming which optimized upper airway patency.